2022
DOI: 10.33448/rsd-v11i9.32251
|View full text |Cite
|
Sign up to set email alerts
|

Simplificação terapêutica com lamivudina e dolutegravir em pacientes vivendo com HIV no Ceará (Estudo LAMDO)

Abstract: O Ministério da Saúde aprovou a dupla terapia (lamivudina associado a um segundo antirretroviral) como opção terapêutica na contraindicação ao uso de outros Inibidores da Transcriptase Reversa Análogos Nucleosídeos - ITRN disponíveis (tenofovir, abacavir e zidovudina) por toxicidade, desde que os pacientes estejam com supressão virológica. Esse trabalho tem o objetivo de avaliar a eficácia na simplificação terapêutica com lamivudina/dolutegravir (3TC/DTG) em pacientes com HIV em terapia antirretroviral (TARV).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Furthermore, studies have shown that a shorter period of viral suppression before switching can increase the risk of virological failure, and since there is no possibility of prior genotyping, dual therapy is recommended as a simplification after efficient virological suppression. (VASCONCELOS et al, 2022). There is no consensus on the initial viral load when choosing dual therapy as a therapeutic option.…”
Section: Efficacymentioning
confidence: 99%
“…Furthermore, studies have shown that a shorter period of viral suppression before switching can increase the risk of virological failure, and since there is no possibility of prior genotyping, dual therapy is recommended as a simplification after efficient virological suppression. (VASCONCELOS et al, 2022). There is no consensus on the initial viral load when choosing dual therapy as a therapeutic option.…”
Section: Efficacymentioning
confidence: 99%